Hydroisomerization catalyst as well as preparation method and application thereof
By using composite molecular sieve with core-shell structure and hydroisomerized catalysts of active metals, the problem of poor catalytic effect of Fischer-Tropsch heavy wax in the prior art is solved, and lubricating oil base oil production with high yield, low pour point, high viscosity index and good oxidative stability is achieved.
Patent Information
- Application Number
- CN202411706904.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing hydroisomerization catalysts have poor isomerization effect when catalyzing Fischer-Tropsch heavy wax (>580℃), and the catalytic process is complicated. The resulting lubricating oil base oil has a low yield, a high pour point, a low viscosity index, and poor oxidation stability.
The composite molecular sieve with a core-shell structure is used as a support and the active metal is supported on its surface. The hydroisomerization catalyst formed cooperates with each other through the shell and inner core of a specific mass ratio to promote the isomerization reaction.
The selectivity of hydroisomer products is improved, and the catalyzed Fischer-Tropsch heavy wax shows a higher yield, and the prepared lubricating oil base oil has a lower pour point, a higher viscosity index, and excellent oxidative stability.
Smart Images

Figure BDA0005154714260000171 
Figure BDA0005154714260000172 
Figure BDA0005154714260000181
Abstract
Description
Technical Field
[0001] The present invention relates to the field of molecular sieves and hydroisomerization catalysts, and in particular to a hydroisomerization catalyst and a preparation method and application thereof. Background Art
[0002] The indirect coal liquefaction process is a process in which coal is gasified, converted, purified, and reacted with Fischer-Tropsch synthesis to produce oil products and chemicals. The intermediate products of Fischer-Tropsch synthesis are rich in olefins. The hydrorefined wax and hydrocracking soft wax obtained after hydrogenation and saturation are mainly straight-chain alkanes, with a high content of saturated hydrocarbons (≥90%), and basically free of impurities such as aromatics, sulfur, and nitrogen, which are suitable for the production of high-quality, high-value-added lubricant base oil products.
[0003] The light fraction (350-550°C) in refined wax and cracked soft wax is easy to hydroisomerize, suitable for the production of low-viscosity base oil, and the process technology is relatively mature. However, for heavy fractions (>580°C), due to their large molecular weight, long chain length, and complex structure, the difficulty of hydroisomerization increases significantly, especially requiring hydroisomerization catalysts with stronger isomerization ability and higher activity stability. At present, the catalysts in the prior art are mainly targeted at light fractions, and it is difficult to effectively process heavy fractions, resulting in unsatisfactory yields and performance of high-viscosity lubricating base oils prepared from Fischer-Tropsch heavy wax.
[0004] The currently reported catalysts, such as the method proposed in CN112111300A, can catalyze the heavy fraction (500-530°C) in the Fischer-Tropsch hydrocracking soft wax, but two hydrogenation isomerizations are required during the catalysis, and the heavy fraction is secondly isomerized and mixed with the light fraction for feeding, making it difficult to obtain a high-yield base oil, and the final product does not disclose the relevant data of the high-viscosity base oil. In addition, although the scheme disclosed in the prior art has made breakthroughs in improving the isomerization selectivity and yield, the preparation process of the catalyst is complicated and the cost is high; and although CN117625238A can produce lubricating oil base oil, the composite molecular sieve disclosed therein is obtained by physical mixing, and it is difficult to control the uniform distribution of the acid sites of the ZSM-48 molecular sieve and the MCM-41 molecular sieve, which affects the isomerization effect. Therefore, developing an efficient hydroisomerization catalyst for Fischer-Tropsch heavy wax (>580℃) and a matching high-viscosity lubricant base oil production process to improve the conversion rate and isomerization selectivity of heavy wax oil products, reduce production costs, optimize the process flow, and thus produce lubricant base oil with high yield, low pour point, high viscosity index and good oxidation stability has become an important technical issue to be urgently solved in the coal chemical industry. Summary of the invention
[0005] The main purpose of the present invention is to provide a hydroisomerization catalyst and a preparation method and application thereof, so as to solve the problems that the hydroisomerization catalyst in the prior art has poor isomerization effect when catalyzing Fischer-Tropsch heavy wax (>580℃), the hydroisomerization catalytic process is complicated, and the lubricating oil base oil obtained by hydroisomerization has low yield, high pour point, low viscosity index and poor oxidation stability.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a hydroisomerization catalyst is provided, which comprises a carrier and an active metal loaded on the carrier, wherein the carrier comprises a composite molecular sieve; the composite molecular sieve comprises an inner core and an outer shell, and the outer shell is coated on the outer surface of the inner core, and the mass ratio of the outer shell to the inner core is 1:(1-10); the inner core comprises a ZSM series molecular sieve and / or a SAPO series molecular sieve, and the outer shell comprises a ZSM series molecular sieve and / or a SAPO series molecular sieve.
[0007] Furthermore, the mass ratio of the active metal to the carrier is 0.3-0.5:100.
[0008] Furthermore, the ZSM series molecular sieves include at least one of ZSM-22, ZSM-23, and ZSM-48.
[0009] Furthermore, the SAPO series molecular sieves include at least one of SAPO-11 and SAPO-31.
[0010] Furthermore, the composite molecular sieve includes at least one of ZSM-48 / ZSM-48, SAPO-11 / ZSM-48, ZSM-23 / ZSM-48, and ZSM-22 / ZSM-48.
[0011] Furthermore, the specific surface area of the composite molecular sieve is 230 to 300 m 2 / g.
[0012] Furthermore, the pore volume of the composite molecular sieve is 0.2 to 0.6 cm3 / g.
[0013] Furthermore, the average pore size of the composite molecular sieve is 3 to 10 nm.
[0014] Furthermore, the weak acid content of the composite molecular sieve is 0.10-0.30 mmol / g, and the medium-strong acid content is 0.05-0.25 mmol / g.
[0015] Furthermore, the carrier also includes a binder.
[0016] Furthermore, the binder is pseudo-boehmite.
[0017] Furthermore, the mass ratio of the composite molecular sieve to the binder is (50-70): (50-30).
[0018] According to another aspect of the present invention, a method for preparing a hydroisomerization catalyst is provided, comprising the following steps: providing a carrier, mixing a precursor solution containing an active metal with the carrier to load the active metal on the carrier, and calcining once to obtain the hydroisomerization catalyst; wherein the carrier comprises a composite molecular sieve.
[0019] Furthermore, the preparation method of the composite molecular sieve includes the following steps: step S1, mixing a first aluminum source, a first silicon source, a first alkali source, a first template, an optional first phosphorus source and water to form gel A, and crystallizing gel A once to obtain a crystallized product A; step S2, mixing a second aluminum source, a second silicon source, a second alkali source, a second template, an optional second phosphorus source and water to form gel B, and crystallizing gel B twice to obtain a crystallized product B; step S3, mixing the crystallized product A and the crystallized product B, crystallizing them three times, and calcining them twice to obtain a composite crystallized product; step S4, sequentially subjecting the composite crystallized product to alkali treatment and / or acid treatment, ion exchange with an ammonium salt solution, and drying to obtain a composite molecular sieve.
[0020] Furthermore, in step S1, the temperature of the first crystallization is 100-180° C., and the time of the first crystallization is 10-60 hours.
[0021] Furthermore, in step S2, the temperature of the secondary crystallization is 100-180° C., and the time of the secondary crystallization is 10-60 hours.
[0022] Furthermore, in step S3, the mass ratio of the crystallization product A to the crystallization product B is 1:(1-10).
[0023] Furthermore, in step S3, the time for the third crystallization is 100-180° C., and the time for the third crystallization is 6-48 hours.
[0024] Furthermore, in step S3, the temperature of the secondary calcination is 500-600° C., and the time of the secondary calcination is 6-10 hours.
[0025] Furthermore, in step S4, the temperature of the alkali treatment is 50-80° C., and the time of the alkali treatment is 2-5 hours.
[0026] Furthermore, in step S4, the temperature of the acid treatment is 50-80° C., and the time of the acid treatment is 2-5 hours.
[0027] Furthermore, in step S4, the concentration of the ammonium salt solution is 1-2 mol / L.
[0028] Furthermore, in step S4, the mass ratio of the composite crystallization product to the ammonium salt solution is 1:15-20.
[0029] Furthermore, in step S4, the ammonium salt solution includes at least one of an ammonium chloride solution and an ammonium nitrate solution.
[0030] Furthermore, in step S4, the temperature of ion exchange is 70-80° C., and the time of ion exchange is 2-4 hours.
[0031] Furthermore, the carrier also includes a binder, and the preparation method of the carrier includes: mixing the composite molecular sieve and the binder and molding to obtain the carrier; wherein the binder is pseudo-boehmite.
[0032] Furthermore, the mass ratio of the composite molecular sieve to the binder is (50-70): (50-30).
[0033] Furthermore, the mass ratio of the active metal to the carrier is 0.3-0.5:100.
[0034] Furthermore, the precursor solution containing active metals includes at least one of chloroplatinic acid solution, tetraammineplatinum dichloride solution, tetraammineplatinum dinitrate solution, and palladium chloride solution.
[0035] Furthermore, the primary calcination temperature is 350-500° C., and the primary calcination time is 4-6 hours.
[0036] According to the third aspect of the present invention, there is provided an application of the hydroisomerization catalyst provided in the first aspect or the hydroisomerization catalyst obtained by the preparation method provided in the second aspect in hydroisomerization of Fischer-Tropsch heavy wax, wherein the Fischer-Tropsch heavy wax comprises refined wax and / or cracked soft wax; the reaction conditions for hydroisomerization are as follows: reaction temperature of 280-360°C, hydrogen partial pressure of 2-10MPa, volume space velocity of 0.1-2h-1, and hydrogen-to-oil volume ratio of (200-1500):1.
[0037] By applying the technical solution of the present invention, the hydroisomerization catalyst provided in the present application includes a carrier and an active metal. The hydroisomerization catalyst is a bifunctional catalyst. The active metal can provide metal sites for hydrogenation and dehydrogenation. The carrier is a composite molecular sieve with a core-shell structure. The composite molecular sieve formed by the synergistic interaction of an outer shell and an inner core in a specific mass ratio can promote the isomerization reaction, so that the Fischer-Tropsch heavy wax (>580°C) shows a higher yield during hydroisomerization, and the prepared lubricating oil base oil has a lower pour point, a higher viscosity index, and excellent oxidation stability.
[0038] Therefore, the present application adopts a composite molecular sieve with a core-shell structure as a carrier and loads active metals on its surface. The formed hydroisomerization catalyst improves the selectivity of the hydroisomerization product, thereby preparing a lubricating oil base oil with a lower pour point, higher viscosity and good oxidation stability in the process of catalyzing the hydroisomerization of Fischer-Tropsch heavy wax (>580°C). DETAILED DESCRIPTION
[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0040] As analyzed in the background technology of this application, the prior art has problems such as poor isomerization effect of hydroisomerization catalysts when catalyzing Fischer-Tropsch heavy wax (>580°C), complex hydroisomerization catalytic process, low yield of lubricating oil base oil obtained by hydroisomerization, high pour point, low viscosity index, and poor oxidation stability. In order to solve the above problems, this application provides a hydroisomerization catalyst and its preparation method and application.
[0041] In a first typical embodiment of the present application, a hydroisomerization catalyst is provided, which includes a carrier and an active metal loaded on the carrier, the carrier includes a composite molecular sieve; the composite molecular sieve includes an inner core and an outer shell, and the outer shell is coated on the outer surface of the inner core; the mass ratio of the outer shell to the inner core is 1:(1 to 10); the inner core includes a ZSM series molecular sieve and / or a SAPO series molecular sieve, and the outer shell includes a ZSM series molecular sieve and / or a SAPO series molecular sieve.
[0042] The hydroisomerization catalyst provided in the present application includes a carrier and an active metal. The hydroisomerization catalyst is a bifunctional catalyst. The active metal can provide metal sites for hydrogenation and dehydrogenation. The carrier is a composite molecular sieve with a core-shell structure. The composite molecular sieve formed by the synergistic interaction of an outer shell and an inner core in a specific mass ratio can promote the isomerization reaction, so that Fischer-Tropsch heavy wax (>580°C) shows a higher yield during hydroisomerization, and the prepared lubricating oil base oil has a lower pour point, a higher viscosity index, and excellent oxidation stability.
[0043] Therefore, the present application adopts a composite molecular sieve with a core-shell structure as a carrier and loads active metals on its surface. The formed hydroisomerization catalyst improves the selectivity of the hydroisomerization product, thereby preparing a lubricating oil base oil with a lower pour point, higher viscosity and good oxidation stability in the process of catalyzing the hydroisomerization of Fischer-Tropsch heavy wax (>580°C).
[0044] The present application regulates the pore structure and acidity distribution of the core and shell of the composite molecular sieve so that the core has a larger pore size and weaker acidity, and the shell has a smaller pore size and stronger acidity (the acid strength of the shell is greater than the acid strength of the core, and the average pore size of the shell is less than the average pore size of the core). The core and the shell cooperate with each other to optimize the diffusion and reaction process of long-chain normal alkanes on the hydroisomerization catalyst, and effectively improve the selectivity of Fischer-Tropsch heavy wax in hydroisomerization. Among them, the stronger acidity on the shell causes the long-chain normal alkanes to be slightly isomerized, generating a large number of single-branched isomers, accompanied by a small amount of cracking reaction in the process. The smaller pore size on the shell has a higher selectivity for the diffusion of single-branched isomers into the core, and can avoid the diffusion of other structural alkanes to the core to affect the degree of isomerization. The generated single-branched isomers diffuse inward to the core with weaker acidity and larger pore size to continue the isomerization reaction and generate multi-branched isomers. The weaker acidity on the core reduces the occurrence of cracking reactions and improves the isomerization selectivity of multi-branched isomers. The multi-branched isomers that have completed the isomerization reaction diffuse to the outer shell through the larger pores on the inner core due to the increased degree of isomerization, while the unreacted or low-isomerized alkanes on the outer shell diffuse to the smaller pores on the outer shell for shape-selective isomerization.
[0045] Typically but not limiting, in the composite molecular sieve provided in the present application, the mass ratio of the outer shell to the inner core is, for example, 1:1, 1:2, 1:4, 1:6, 1:8, 1:10 or a range consisting of any two values.
[0046] In order to further improve the conversion rate of the hydroisomerization reaction and the selectivity of the hydroisomerization product, the mass ratio of the active metal to the carrier is preferably 0.3 to 0.5:100.
[0047] Typically but not limitatively, in the hydroisomerization catalyst provided in the present application, the mass ratio of active metal to carrier is, for example, 0.3:100, 0.35:100, 0.4:100, 0.45:100, 0.5:100 or a range consisting of any two values.
[0048] In order to further improve the isomerization performance of the composite molecular sieve, the ZSM series molecular sieves preferably include any one or more of ZSM-22, ZSM-23, and ZSM-48, and the SAPO series molecular sieves preferably include any one or more of SAPO-11 and SAPO-31.
[0049] In order to further make the number of acidic sites on the composite molecular sieve moderate, the silicon-aluminum ratio of ZSM-22 is preferably 40 to 140:1, the silicon-aluminum ratio of ZSM-23 is preferably 40 to 130:1, the silicon-aluminum ratio of ZSM-48 is preferably 100 to 180:1, the silicon-aluminum ratio of SAPO-11 is preferably 0.4 to 0.8:1, and the silicon-aluminum ratio of SAPO-31 is preferably 0.3 to 0.9:1.
[0050] The silicon-aluminum ratio in this application refers to the "molar ratio of SiO2 to Al2O3 in the molecular sieve".
[0051] Among them, when ZSM-22 is used as the outer shell, the silicon-aluminum ratio is 40-130:1, and when ZSM-22 is used as the inner core, the silicon-aluminum ratio is 90-140:1; when ZSM-23 is used as the outer shell, the silicon-aluminum ratio is 40-110:1, and when ZSM-23 is used as the inner core, the silicon-aluminum ratio is 80-130:1; when ZSM-48 is used as the outer shell, the silicon-aluminum ratio is 100-150:1, and when ZSM-48 is used as the inner core, the silicon-aluminum ratio is 130-180:1; when SAPO-11 is used as the outer shell, the silicon-aluminum ratio is 0.4-0.6:1, and when SAPO-11 is used as the inner core, the silicon-aluminum ratio is 0.6-0.8:1; when SAPO-31 is used as the outer shell, the silicon-aluminum ratio is 0.3-0.6:1, and when SAPO-31 is used as the inner core, the silicon-aluminum ratio is 0.6-0.9:1; when the molecular sieve types of the inner core and the outer shell are the same, the silicon-aluminum ratio of the inner core is greater than the silicon-aluminum ratio of the outer shell.
[0052] Typically, but not limiting, the silicon-aluminum ratio of ZSM-22 is 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1 or a range consisting of any two of these numbers.
[0053] Typically, but not limiting, the silicon-aluminum ratio of ZSM-23 is 40:1, 60:1, 80:1, 100:1, 120:1, 140:1 or a range consisting of any two of these numbers.
[0054] Typically, but not limiting, the silicon-aluminum ratio of ZSM-48 is 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1 or a range consisting of any two of these numbers.
[0055] Typically, but not limiting, the silicon-aluminum ratio of SAPO-11 is 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1 or a range consisting of any two of these numbers.
[0056] Typically, but not limiting, the silicon-aluminum ratio of SAPO-31 is 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or a range consisting of any two of these values.
[0057] In order to further enhance the hydroisomerization effect of the hydroisomerization catalyst when catalyzing Fischer-Tropsch heavy oil, the composite molecular sieve preferably includes at least one of ZSM-48 / ZSM-48, SAPO-11 / ZSM-48, ZSM-23 / ZSM-48, and ZSM-22 / ZSM-48. It is further preferred that the composite molecular sieve is ZSM-48 / ZSM-48 to further enhance the hydroisomerization effect of Fischer-Tropsch heavy oil.
[0058] The above “ / ” means “shell and core”. For example, the above “ZSM-48 / ZSM-48” means that the shell of the composite molecular sieve is ZSM-48 and the core is ZSM-48; for example, the above “SAPO-11 / ZSM-48” means that the shell of the composite molecular sieve is SAPO-11 and the core is ZSM-48.
[0059] In some implementations, the specific surface area of the composite molecular sieve is 230 to 300 m 2 / g; for example 230m 2 / g, 250m 2 / g, 270m 2 / g, 290m 2 / g、300m 2 / g, and any value in the range formed by any two of the above values.
[0060] In some implementations, the pore volume of the composite molecular sieve is 0.2 to 0.6 cm 3 / g; for example 0.2cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, and any value in the range formed by any two of the above values.
[0061] In some embodiments, the average pore size of the composite molecular sieve is 3-10 nm, for example 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, and any value in the range formed by any two of the above values.
[0062] In some embodiments, the weak acid amount of the composite molecular sieve is 0.10-0.30 mmol / g (such as 0.10 mmol / g, 0.15 mmol / g, 0.20 mmol / g, 0.25 mmol / g, 0.30 mmol / g, or a range consisting of any two numerical values), and the medium-strong acid amount is 0.05-0.25 mmol / g (such as 0.05 mmol / g, 0.10 mmol / g, 0.15 mmol / g, 0.20 mmol / g, 0.25 mmol / g, or a range consisting of any two numerical values).
[0063] Among them, the NH3-TPD method is used to characterize the acid strength and acid amount. The desorption peaks at different temperatures correspond to acids of different strengths, and the peak area corresponds to the acid amount. On the NH3-TPD spectrum, weak acids correspond to NH3 desorption peaks between 100 and 250°C, and medium-strong acids correspond to NH3 desorption peaks between 250 and 450°C.
[0064] In some embodiments, the carrier of the hydroisomerization catalyst provided in the present application further includes a binder to allow multiple composite molecular sieve particles to bond to each other and improve the strength of the carrier. In order to further improve the strength of the carrier while maintaining a high isomerization performance, the mass ratio of the composite molecular sieve to the binder is preferably (50-70): (50-30). In order to further improve the performance of the binder, the binder preferably includes pseudo-boehmite and / or SB powder.
[0065] Typically but not limiting, the mass ratio of the composite molecular sieve to the binder is, for example, 50:50, 55:45, 60:40, 65:35, 70:30 or a range consisting of any two values.
[0066] In order to further improve the hydrodehydrogenation performance of the hydroisomerization catalyst, the active metal supported on the carrier is preferably a noble metal, and more preferably the noble metal includes platinum and / or palladium.
[0067] In another typical embodiment of the present application, a method for preparing a hydroisomerization catalyst is provided, comprising the following steps: providing a carrier, mixing a precursor solution containing an active metal with the carrier to load the active metal on the carrier, and calcining once to obtain the hydroisomerization catalyst; wherein the carrier comprises a composite molecular sieve.
[0068] The preparation method is easy to operate, improves production efficiency, meets market demand, and is suitable for industrial production.
[0069] In some embodiments, the preparation method of the composite molecular sieve includes the following steps: step S1, mixing a first aluminum source, a first silicon source, a first alkali source, a first template, an optional first phosphorus source and water to form gel A, and crystallizing gel A once to obtain a crystallized product A; step S2, mixing a second aluminum source, a second silicon source, a second alkali source, a second template, an optional second phosphorus source and water to form gel B, and crystallizing gel B twice to obtain a crystallized product B; step S3, mixing the crystallized product A and the crystallized product B for a third crystallization, and calcining twice to obtain a composite crystallized product; step S4, sequentially subjecting the composite crystallized product to alkali treatment and / or acid treatment, ion exchange with an ammonium salt solution, and drying to obtain a composite molecular sieve.
[0070] The present application prepares a composite molecular sieve with a core-shell structure by the preparation method of the above-mentioned composite molecular sieve. Among them, the acidity of the core and shell of the composite molecular sieve is adjusted by regulating the silicon-aluminum ratio of the core and the shell. The larger the silicon-aluminum ratio, the weaker the acidity. Conversely, the smaller the silicon-aluminum ratio, the stronger the acidity. The pore size of the core and the outer core is adjusted by regulating the type or amount of the template, alkali treatment and / or acid treatment. Among them, an alkaline solution is used for alkali treatment to remove silicon from the composite crystallization product, thereby destroying the original pore structure in the composite crystallization product, increasing the pore size, improving the mass transfer effect, and further improving the selectivity of multi-branched isomers. Acid treatment is performed with an acidic solution to remove amorphous oxides from the composite crystallization product. The gradient pore distribution and acid strength of the composite molecular sieve are regulated by the above method, so that the acid strength of the shell in the prepared composite molecular sieve is greater than the acid strength of the core, and the average pore size of the shell is smaller than the average pore size of the core.
[0071] In the present application, the first aluminum source and the second aluminum source used may be suitable for preparing the composite molecular sieve of the present application. Preferably, the first aluminum source and the second aluminum source independently include any one or more of sodium aluminate, aluminum sulfate, and pseudo-boehmite.
[0072] In the present application, the first silicon source and the second silicon source used may be suitable for preparing the composite molecular sieve of the present application. Preferably, the first silicon source and the second silicon source independently include any one or more of silica sol, tetraethyl orthosilicate, and sodium silicate.
[0073] In the present application, the first alkali source and the second alkali source used may be suitable for preparing the composite molecular sieve of the present application. Preferably, the first alkali source and the second alkali source independently include any one or more of sodium hydroxide, potassium hydroxide, and ammonia water.
[0074] In the present application, the first phosphorus source and the second phosphorus source used may be suitable for preparing the composite molecular sieve of the present application. Preferably, the first phosphorus source and the second phosphorus source are independently phosphoric acid.
[0075] In the present application, the first template used is suitable for preparing the composite molecular sieve of the present application. Preferably, the first template includes any one or more of hexamethylammonium bromide, 1,6-hexanediamine, pyrrolidine, isopropylamine, diethylamine, and di-n-butylamine.
[0076] In the present application, the second template used is suitable for preparing the composite molecular sieve of the present application. Preferably, the second template includes any one or more of hexamethylammonium bromide, 1,6-hexanediamine, pyrrolidine, isopropylamine, diethylamine, and di-n-butylamine.
[0077] In some embodiments, when the core or shell of the composite molecular sieve is ZSM-48, the preferred template agent is hexamethylammonium bromide; when the core or shell of the composite molecular sieve is ZSM-22, the preferred template agent is 1,6-hexanediamine; when the core or shell of the composite molecular sieve is ZSM-23, the preferred template agent is pyrrolidine or isopropylamine; when the core or shell of the composite molecular sieve is SAPO-11, the preferred template agent is diethylamine; when the core or shell of the composite molecular sieve is SAPO-31, the preferred template agent is di-n-butylamine.
[0078] Crystallization treatment can promote the formation and growth of molecular sieve crystals. In order to further improve the quality and purity of the crystal product A, it is preferred that in step S1, the temperature of the first crystallization is 100-180°C and the time of the first crystallization is 10-60h. Similarly, in order to further improve the quality and purity of the crystal product B, it is preferred that the temperature of the second crystallization is 100-180°C and the time of the second crystallization is 10-60h.
[0079] Typically but not limiting, the temperature of the primary crystallization is 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a range consisting of any two values; the time of the primary crystallization is 10h, 20h, 30h, 40h, 50h, 60h or a range consisting of any two values; the temperature of the secondary crystallization is 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a range consisting of any two values; the time of the secondary crystallization is 10h, 20h, 30h, 40h, 50h, 60h or a range consisting of any two values.
[0080] In some embodiments, after the completion of the first crystallization, the second crystallization, and the third crystallization, solid-liquid separation, washing, and drying are performed independently and sequentially to remove impurities on the surface of the crystallization product to further ensure the purity of the crystallization product, wherein solid-liquid separation, washing, and drying are conventional operations in the field and will not be repeated here.
[0081] In order to further improve the isomerization effect of the composite molecular sieve, the mass ratio of the crystallized product A to the crystallized product B is preferably 1:(1-10);
[0082] Typically but not limiting, the mass ratio of crystallized product A to crystallized product B is, for example, 1:1, 1:2, 1:4, 1:6, 1:8, 1:10 or a range consisting of any two values.
[0083] In order to further improve the quality, purity and crystal morphology of the composite crystal product, it is preferred that the time for the third crystallization is 100-180° C. and the time for the third crystallization is 6-48 h.
[0084] Typically but not limiting, the time for the three crystallizations is 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a range consisting of any two values; the time for the three crystallizations is 6h, 14h, 22h, 30h, 38h, 46h or a range consisting of any two values.
[0085] In order to further improve the activity of the composite crystal product, the secondary calcination temperature is preferably 500-600° C. and the secondary calcination time is 6-10 h.
[0086] Typically but not limiting, the secondary calcination temperature is 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or a range consisting of any two values; the secondary calcination time is 6h, 7h, 8h, 9h, 10h or a range consisting of any two values.
[0087] In order to further regulate the pore structure of the composite molecular sieve, the alkali treatment temperature is preferably 50-80°C, and the alkali treatment time is 2-5h; preferably, an alkaline solution is used for the alkali treatment, and further preferably, the concentration of the alkaline solution is 0.1-0.5 mol / L, and further preferably, the mass ratio of the composite crystallization product to the alkaline solution is 1:(15-20), and further preferably, the alkaline solution includes any one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and ammonia aqueous solution.
[0088] Typically but not limiting, the temperature of the alkali treatment is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two values; the time of the alkali treatment is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range consisting of any two values. The concentration of the alkaline solution is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L or a range consisting of any two values.
[0089] In order to further regulate the pore structure of the composite molecular sieve, the acid treatment temperature is preferably 50-80°C, and the acid treatment time is 2-5h; preferably, an acid solution is used for acid treatment, and the concentration of the acid solution is further preferably 0.05-0.5 mol / L, and the mass ratio of the composite crystallization product to the acid solution is further preferably 1:(15-20), and the acid solution further preferably includes any one or more of aqueous hydrochloric acid solution, aqueous nitric acid solution, aqueous phosphoric acid solution, and aqueous citric acid solution.
[0090] Typically, but not limiting, the temperature of the acid treatment is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, or a range consisting of any two values; the time of the acid treatment is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a range consisting of any two values. The concentration of the acid solution is 0.05mol / L, 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, or a range consisting of any two values.
[0091] In order to further promote the exchange of metal ions and ammonium ions in the composite crystallization product, the preferred ion exchange temperature is 70-80°C, and the preferred ion exchange time is 2-4h; the preferred concentration of the ammonium salt solution is 1-2 mol / L, and the preferred mass ratio of the composite crystallization product to the ammonium salt solution is 1:15-20.
[0092] The above ammonium salt solution is not specifically limited, and any ammonium salt solution commonly used for ion exchange in the art can be used, including but not limited to any one or more of ammonium chloride solution and ammonium nitrate solution.
[0093] Typically, but not limiting, the ion exchange temperature is 70°C, 72°C, 74°C, 76°C, 78°C, 80°C or a range consisting of any two values, and the ion exchange time is 2h, 2.5h, 3h, 4h or a range consisting of any two values.
[0094] In some embodiments, the carrier further includes a binder, and the preparation method of the carrier includes: mixing the composite molecular sieve with the binder and molding to obtain the carrier; wherein the binder includes at least one of pseudo-boehmite and SB powder. The composite molecular sieve is mixed with the binder so that multiple composite molecular sieve particles are bonded to each other to improve the strength of the carrier.
[0095] In order to further improve the performance of the binder, the binder preferably includes pseudo-boehmite and / or SB powder. In order to further improve the strength of the carrier and maintain high isomerization performance, the mass ratio of the composite molecular sieve to the binder is preferably (50-70): (50-30).
[0096] In some embodiments, a precursor solution containing an active metal is mixed with a support, and the active metal is loaded on the support by an equal volume impregnation method to further promote uniform dispersion of the metal on the support.
[0097] In order to further improve the hydrodehydrogenation activity, the mass ratio of active metal to carrier is preferably 0.3-0.5:100; it is further preferred that the active metal is a noble metal, and it is further preferred that the noble metal includes platinum and / or palladium to further promote the enhancement of the hydrodehydrogenation activity.
[0098] Typically but not limiting, the mass ratio of the composite molecular sieve to the binder is, for example, 50:50, 55:45, 60:40, 65:35, 70:30 or a range consisting of any two values; the mass ratio of the active metal to the carrier is, for example, 0.3:100, 0.35:100, 0.4:100, 0.45:100, 0.5:100 or a range consisting of any two values.
[0099] The precursor solution containing active metals in the present application is not specifically limited, and any platinum-containing solution or palladium-containing solution commonly used in the art may be used, including but not limited to chloroplatinic acid solution, tetraammineplatinum dichloride solution, tetraammineplatinum dinitrate solution, palladium chloride solution, etc.
[0100] In order to improve the stability and activity of the hydroisomerization catalyst, the primary calcination temperature is preferably 350-500°C and the primary calcination time is 4-6 hours. Preferably, drying is also included before the primary calcination to prevent the destruction of the catalyst structure caused by violent gas release during the high-temperature calcination process. It is further preferred that the drying temperature is 80-120°C and the drying time is 2-4 hours.
[0101] In a third typical embodiment of the present application, a hydroisomerization catalyst is provided for use in hydroisomerization of Fischer-Tropsch heavy wax, wherein the hydroisomerization catalyst is derived from the hydroisomerization catalyst provided in the first typical embodiment or the hydroisomerization catalyst obtained by the preparation method provided in the second typical embodiment; the Fischer-Tropsch heavy wax includes refined wax and / or cracked soft wax; the reaction conditions for hydroisomerization are: reaction temperature of 280-360°C, hydrogen partial pressure of 2-10 MPa, and volume space velocity of 0.1-2 h -1 , the volume ratio of hydrogen to oil is (200~1500):1.
[0102] In order to further improve the conversion rate of the hydroisomerization reaction and the yield of the product, the preferred reaction conditions for the hydroisomerization are: reaction temperature of 300-350°C, hydrogen partial pressure of 3-8 MPa, and volume space velocity of 0.5-1.6 h -1 , the volume ratio of hydrogen to oil is (500~1200):1.
[0103] In some embodiments, the catalyst used for preparing lubricating oil base oil from Fischer-Tropsch heavy wax also includes a supplementary refining catalyst, which includes a carrier and an active metal loaded on the carrier, the carrier includes alumina and / or silica aluminum, preferably alumina; the active metal includes any one or more of Pt, Pd, Ni, W, preferably Pt and / or Pd; based on the total mass of the carrier as 100%, the loading amount of the active metal is 0.3 to 1 wt%.
[0104] The supplementary refined catalyst in this application can be purchased from the market (Fujian Institute precious metal FMTA-2 catalyst), or prepared by the following steps:
[0105] In some embodiments, pseudo-boehmite is used as a carrier and SB powder is used as an additive, and mixed with a precursor solution containing Pt metal and / or a precursor solution containing Pd metal to load precious metals Pt and / or Pd, and then a supplementary refined catalyst is obtained by roasting, wherein the loading amount of active metal is 0.3-1wt%.
[0106] In the process of preparing lubricating base oil from Fischer-Tropsch heavy wax, a hydroisomerization catalyst is used for a hydroisomerization reaction, and then a supplementary refining catalyst is used for a supplementary refining reaction to hydrogenate and saturate the olefins in the hydroisomerization product into alkanes, so that the performance of the obtained lubricating base oil is better.
[0107] In some embodiments, the reaction conditions for supplementary refining are: reaction temperature is 200-280°C, preferably 220-260°C; volume space velocity is 0.2-2h -1 , preferably 0.5 to 1.6 hours -1 ; The hydrogen-oil volume ratio is (200-1500):1, preferably (500-1200):1; the hydrogen partial pressure is 2-10MPa, preferably 3-8MPa.
[0108] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0109] Example 1
[0110] The present embodiment provides a hydroisomerization catalyst, which includes a carrier and metal platinum loaded on the carrier, the mass ratio of metal platinum to the carrier is 0.5:100, the carrier is a composite molecular sieve and pseudo-boehmite, and the ratio of the two is 65:35; the composite molecular sieve includes a core and an outer shell, and the outer shell is coated on the outer surface of the inner core, and the mass ratio of the outer shell to the inner core is 1:3; wherein the outer shell is a ZSM-48 molecular sieve, the silicon-aluminum ratio of the outer shell is 130, and the inner core is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the inner core is 150; after measurement, the specific surface area of the composite molecular sieve is 252m 2 / g, pore volume is 0.48cm 3 / g, the average pore size is 8.3nm, the weak acid content is 0.18mmol / g, and the medium-strong acid content is 0.11mmol / g.
[0111] The preparation method of the hydroisomerization catalyst comprises the following steps:
[0112] (1) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0077:1:0.12:0.022:25, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 160° C. for 10 h, filtered, washed with deionized water, and dried at 120° C. for 6 h to obtain a crystallized product A.
[0113] (2) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0067:1:0.10:0.018:20, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 155° C. for 12 h, filtered, washed with deionized water, and dried at 120° C. for 4 h to obtain a crystallized product B.
[0114] (3) The crystallized product A and the crystallized product B are mixed and stirred, and then transferred into a crystallization reactor, crystallized at 170° C. for 12 hours, filtered, washed with deionized water, dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a composite crystallized product. The mass ratio of the crystallized product A to the crystallized product B is 1:3.
[0115] (4) Using 0.1 mol / L sodium hydroxide aqueous solution, the composite crystallization product is subjected to alkali treatment for 2 hours at a temperature of 80°C, the mass ratio of the composite crystallization product to the sodium hydroxide aqueous solution is 1:20, and then filtered, washed with deionized water, and dried at 120°C for 4 hours. Then, ion exchange is performed on the composite crystallization product using 1 mol / L ammonium chloride solution, wherein the ion exchange temperature is 80°C, the ion exchange time is 2 hours, and the mass ratio of the composite crystallization product to the ammonium chloride solution is 1:20. After the ion exchange is completed, it is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a composite molecular sieve.
[0116] (5) The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 65:35, and the carrier was prepared by a kneading-extrusion method. The dichlorotetraamineplatinum solution was mixed and stirred with the carrier, and Pt metal was loaded on the carrier by an equal volume impregnation method. The mass ratio of Pt in the dichlorotetraamineplatinum solution to the carrier was 0.5:100. After drying at 120°C for 4h and calcining at 450°C for 6h, a hydroisomerization catalyst was obtained.
[0117] Example 2
[0118] The present embodiment provides a hydroisomerization catalyst, which includes a carrier and metal platinum loaded on the carrier, the mass ratio of the metal platinum to the carrier is 0.45:100, the carrier is a composite molecular sieve and pseudo-boehmite, and the ratio of the two is 60:40; the composite molecular sieve includes a core and an outer shell, and the outer shell is coated on the outer surface of the inner core, and the mass ratio of the outer shell to the inner core is 1:5; wherein the outer shell is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the outer shell is 110; the inner core is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the inner core is 135; the specific surface area of the composite molecular sieve is 236m 2 / g, pore volume is 0.32cm 3 / g, the average pore size is 5.1nm, the weak acid content is 0.15mmol / g, and the medium-strong acid content is 0.12mmol / g.
[0119] The preparation method of the hydroisomerization catalyst comprises the following steps:
[0120] (1) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0091:1:0.12:0.02:20, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 160° C. for 12 h, filtered, washed with deionized water, and dried at 120° C. for 6 h to obtain a crystallized product A.
[0121] (2) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0074:1:0.13:0.021:25, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 160° C. for 10 h, filtered, washed with deionized water, and dried at 120° C. for 4 h to obtain a crystallized product B.
[0122] (3) The crystallized product A and the crystallized product B are mixed and stirred, and then transferred into a crystallization reaction kettle, crystallized at 180° C. for 10 h, filtered, washed with deionized water, dried at 100° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a composite crystallized product. The mass ratio of the crystallized product A to the crystallized product B is 1:5.
[0123] (4) Using 0.2 mol / L sodium hydroxide aqueous solution, the composite crystallization product is subjected to alkali treatment for 2 hours at a temperature of 80°C, the mass ratio of the composite crystallization product to the sodium hydroxide aqueous solution is 1:20, and then filtered, washed with deionized water, and dried at 120°C for 4 hours. Then, 1 mol / L ammonium chloride solution is used to perform ion exchange on the composite crystallization product, wherein the ion exchange temperature is 80°C, the ion exchange time is 2 hours, and the mass ratio of the composite crystallization product to the ammonium chloride solution is 1:20. After the ion exchange is completed, it is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a composite molecular sieve.
[0124] (5) The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 60:40, and the carrier was prepared by a kneading-extrusion method. The dichlorotetraammineplatinum solution was mixed and stirred with the carrier, and Pt metal was loaded on the carrier by an equal volume impregnation method. The mass ratio of Pt in the dichlorotetraammineplatinum solution to the carrier was 0.45:100. After drying at 120°C for 4h and calcining at 450°C for 6h, a hydroisomerization catalyst was obtained.
[0125] Example 3
[0126] The present embodiment provides a hydroisomerization catalyst, which includes a carrier and metal platinum loaded on the carrier, the mass ratio of the metal platinum to the carrier is 0.4:100, the carrier is a composite molecular sieve and pseudo-boehmite, and the ratio of the two is 55:45; the composite molecular sieve includes a core and an outer shell, and the outer shell is coated on the outer surface of the core, and the mass ratio of the outer shell to the core is 1:4; wherein the outer shell is a ZSM-23 molecular sieve, and the silicon-aluminum ratio of the outer shell is 110; the core is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the core is 170; the specific surface area of the composite molecular sieve is 243m 2 / g, pore volume is 0.43cm 3 / g, the average pore size is 7.2nm, the weak acid content is 0.12mmol / g, and the medium-strong acid content is 0.10mmol / g.
[0127] The preparation method of the hydroisomerization catalyst comprises the following steps:
[0128] (1) Aluminum sulfate, silica sol, sodium hydroxide, pyrrolidine and water were mixed in a molar ratio of 0.0091:1:0.15:0.4:30, stirred to form a gel, and the gel was transferred into a crystallization reactor, crystallized at 160° C. for 15 h, filtered, washed with deionized water, and dried at 120° C. for 6 h to obtain a crystallized product A.
[0129] (2) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0059:1:0.14:0.02:30, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 160° C. for 12 h, filtered, washed with deionized water, and dried at 120° C. for 4 h to obtain a crystallized product B.
[0130] (3) The crystallized product A and the crystallized product B are mixed and stirred, and then transferred into a crystallization reactor, crystallized at 180° C. for 20 h, filtered, washed with deionized water, dried at 100° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a composite crystallized product. The mass ratio of the crystallized product A to the crystallized product B is 1:4.
[0131] (4) The composite crystallization product was treated with 0.2 mol / L ammonia solution at 80°C for 2 h, with the mass ratio of the composite crystallization product to the ammonia solution being 1:20, and then filtered, washed with deionized water, and dried at 120°C for 4 h. The composite crystallization product was then ion exchanged with 1 mol / L ammonium chloride solution, wherein the ion exchange temperature was 80°C, the ion exchange time was 2 h, and the mass ratio of the composite crystallization product to the ammonium chloride solution was 1:20. After the ion exchange was completed, the composite molecular sieve was filtered, washed with deionized water, and dried at 120°C for 4 h to obtain the composite molecular sieve.
[0132] (5) The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 55:45, and the carrier was prepared by a kneading-extrusion method. The chloroplatinic acid solution was mixed and stirred with the carrier, and the Pt metal was loaded on the carrier precursor by an equal volume impregnation method. The mass ratio of Pt in the tetraammineplatinum dichloride solution to the carrier was 0.4:100. After drying at 120°C for 4h and calcining at 450°C for 6h, a hydroisomerization catalyst was obtained.
[0133] Example 4
[0134] The present embodiment provides a hydroisomerization catalyst, which includes a carrier and metal platinum loaded on the carrier, the mass ratio of the metal platinum to the carrier is 0.5:100, the carrier is a composite molecular sieve and alumina, and the ratio of the two is 70:30; the composite molecular sieve includes a core and an outer shell, and the outer shell is coated on the outer surface of the core, and the mass ratio of the outer shell to the core is 1:4; wherein the outer shell is a SAPO-11 molecular sieve, and the silicon-aluminum ratio of the outer shell is 0.6; the core is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the core is 120; the specific surface area of the composite molecular sieve is 231m 2 / g, pore volume is 0.29cm 3 / g, the average pore size is 4.7nm, the weak acid content is 0.16mmol / g, and the medium-strong acid content is 0.11mmol / g.
[0135] The preparation method of the hydroisomerization catalyst comprises the following steps:
[0136] (1) Aluminum sulfate, silica sol, sodium hydroxide, phosphoric acid, diethylamine and water were mixed in a molar ratio of 0.0091:1:0.12:0.0073:0.02:20, stirred to form a gel, and the gel was transferred into a crystallization reactor, crystallized at 160° C. for 10 h, filtered, washed with deionized water, and dried at 120° C. for 6 h to obtain a crystallized product A.
[0137] (2) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0083:1:0.09:0.02:20, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 150° C. for 24 h, filtered, washed with deionized water, and dried at 120° C. for 4 h to obtain a crystallized product B.
[0138] (3) The crystallized product A and the crystallized product B are mixed and stirred, and then transferred into a crystallization reactor, crystallized at 180° C. for 16 hours, filtered, washed with deionized water, dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a composite crystallized product. The mass ratio of the crystallized product A to the crystallized product B is 1:4.
[0139] (4) Using 0.2 mol / L ammonia solution, the composite crystallization product is subjected to alkali treatment for 2 hours at a temperature of 80°C, the mass ratio of the composite crystallization product to the ammonia solution is 1:20, and then filtered, washed with deionized water, and dried at 120°C for 4 hours. Then, ion exchange is performed on the composite crystallization product using 1 mol / L ammonium chloride solution, wherein the ion exchange temperature is 80°C, the ion exchange time is 2 hours, and the mass ratio of the composite crystallization product to the ammonium chloride solution is 1:20. After the ion exchange is completed, it is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a composite molecular sieve.
[0140] (5) The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 70:30, and the carrier was prepared by a kneading-extrusion method. The dichlorotetraamineplatinum solution was mixed and stirred with the carrier, and the Pt metal was loaded on the carrier precursor by an equal volume impregnation method. The mass ratio of Pt in the dichlorotetraamineplatinum solution to the carrier was 0.5:100. After drying at 120°C for 4h and calcining at 450°C for 6h, a hydroisomerization catalyst was obtained.
[0141] Example 5
[0142] The present embodiment provides a hydroisomerization catalyst, which includes a carrier and metal platinum loaded on the carrier, the mass ratio of the metal platinum to the carrier is 0.4:100, the carrier is a composite molecular sieve and pseudo-boehmite, and the ratio of the two is 65:35; the composite molecular sieve includes a core and an outer shell, and the outer shell is coated on the outer surface of the core, and the mass ratio of the outer shell to the core is 1:4; wherein the outer shell is a ZSM-22 molecular sieve, and the silicon-aluminum ratio of the outer shell is 80; the core is a ZSM-48 molecular sieve, and the silicon-aluminum ratio of the core is 130; the specific surface area of the composite molecular sieve is 263m 2 / g, pore volume is 0.58cm 3 / g, the average pore size is 9.4nm, the weak acid content is 0.21mmol / g, and the medium-strong acid content is 0.16mmol / g.
[0143] The preparation method of the hydroisomerization catalyst comprises the following steps:
[0144] (1) Aluminum sulfate, silica sol, sodium hydroxide, 1,6-hexanediamine and water were mixed in a molar ratio of 0.0091:1:0.12:0.02:20, stirred to form a gel, and the gel was transferred into a crystallization reactor, crystallized at 160° C. for 10 h, filtered, washed with deionized water, and dried at 120° C. for 6 h to obtain a crystallized product A.
[0145] (2) Sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0077:1:0.13:0.018:25, stirred to form a gel, and the gel is transferred into a crystallization reactor, crystallized at 160° C. for 12 h, filtered, washed with deionized water, and dried at 120° C. for 4 h to obtain a crystallized product B.
[0146] (3) The crystallized product A and the crystallized product B are mixed and stirred, and then transferred into a crystallization reactor, crystallized at 180° C. for 16 hours, filtered, washed with deionized water, dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a composite crystallized product. The mass ratio of the crystallized product A to the crystallized product B is 1:4.
[0147] (4) The composite crystallization product was treated with 0.2 mol / L ammonia solution at 80°C for 2 h, with the mass ratio of the composite crystallization product to the ammonia solution being 1:20, and then filtered, washed with deionized water, and dried at 120°C for 4 h. The composite crystallization product was then ion exchanged with 1 mol / L ammonium chloride solution, wherein the ion exchange temperature was 80°C, the ion exchange time was 2 h, and the mass ratio of the composite crystallization product to the ammonium chloride solution was 1:20. After the ion exchange was completed, the composite molecular sieve was filtered, washed with deionized water, and dried at 120°C for 4 h to obtain the composite molecular sieve.
[0148] (5) The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 65:35, and the carrier was prepared by a kneading-extrusion method. The dichlorotetraamineplatinum solution was mixed and stirred with the carrier, and the Pt metal was loaded on the carrier precursor by an equal volume impregnation method. The mass ratio of Pt in the dichlorotetraamineplatinum solution to the carrier was 0.4:100. After drying at 120°C for 4h and calcining at 420°C for 6h, a hydroisomerization catalyst was obtained.
[0149] Example 6
[0150] The difference from Example 1 is that, in Example 6, the mass ratio of the crystallized product A and the crystallized product B is adjusted so that the mass ratio of the outer shell and the inner core in the composite molecular sieve is 1:1.
[0151] Example 7
[0152] The difference from Example 1 is that, in Example 7, the mass ratio of the crystallized product A and the crystallized product B is adjusted so that the mass ratio of the outer shell to the inner core in the composite molecular sieve is 1:10.
[0153] Example 8
[0154] The difference from Example 1 is that, in Example 8, the amount of tetraamine dichloroplatinum solution is adjusted so that the mass ratio of metal platinum to the carrier is 0.3:100.
[0155] Example 9
[0156] The difference from Example 1 is that, in Example 9, the amount of tetraamine dichloroplatinum solution is adjusted so that the mass ratio of metal platinum to the carrier is 0.5:100.
[0157] Example 10
[0158] The difference from Example 1 is that, in Example 10, the amount of tetraamine dichloroplatinum solution is adjusted so that the mass ratio of metal platinum to the carrier is 0.05:100.
[0159] Embodiment 11
[0160] The difference from Example 1 is that, in Example 11, the amount of tetraamine dichloroplatinum solution is adjusted so that the mass ratio of metal platinum to the carrier is 1.0:100.
[0161] Comparative Example 1
[0162] The preparation method of the composite molecular sieve in Comparative Example 1 is: ZSM-48 molecular sieve A with a silicon-aluminum ratio of 110 and ZSM-48 molecular sieve B with a silicon-aluminum ratio of 135 are mixed to obtain the composite molecular sieve, and the mass ratio of ZSM-48 molecular sieve A to ZSM-48 molecular sieve B is 1:5.
[0163] The composite molecular sieve and pseudo-boehmite were mixed in a mass ratio of 60:40, and the carrier was prepared by the kneading-extrusion method. The dichlorotetraammineplatinum solution was mixed and stirred with the carrier, and the Pt metal was loaded on the carrier by an equal volume impregnation method. The mass ratio of Pt in the dichlorotetraammineplatinum solution to the carrier was 0.5:100. After drying at 120°C for 4h and calcining at 450°C for 6h, a hydroisomerization catalyst was obtained.
[0164] The preparation method of ZSM-48 molecular sieve A includes the following steps: mixing sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water in a molar ratio of 0.0091:1:0.12:0.02:20, stirring to form a gel, transferring the gel into a crystallization reactor, crystallizing at 180°C for 24 hours, filtering, washing with deionized water, and drying at 120°C for 6 hours to obtain ZSM-48 molecular sieve A.
[0165] The preparation method of ZSM-48 molecular sieve B comprises the following steps: sodium aluminate, silica sol, sodium hydroxide, hexamethylammonium bromide and water are mixed in a molar ratio of 0.0074:1:0.13:0.021:25, stirred to form a gel, transferred the gel into a crystallization reactor, crystallized at 180°C for 20 hours, filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain ZSM-48 molecular sieve B.
[0166] Comparative Example 2
[0167] The difference from Comparative Example 1 is that the composite molecular sieve in Comparative Example 2 only contains ZSM-48 molecular sieve with a silicon-aluminum ratio of 135.
[0168] Comparative Example 3
[0169] The difference from Comparative Example 1 is that the composite molecular sieve in Comparative Example 3 only contains ZSM-48 molecular sieve with a silicon-aluminum ratio of 110.
[0170] Comparative Example 4
[0171] The difference from the preparation method of Example 1 is that, in Comparative Example 4, the mass ratio of the crystallized product A and the crystallized product B is adjusted so that the mass ratio of the outer shell and the inner core in the composite molecular sieve is 1:0.1.
[0172] Comparative Example 5
[0173] The difference from the preparation method of Example 1 is that in Comparative Example 5, the mass ratio of the crystallized product A and the crystallized product B is adjusted so that the mass ratio of the outer shell to the inner core in the composite molecular sieve is 1:15.
[0174] Test Example 1
[0175] The hydroisomerization catalysts prepared in Examples 1-11 and Comparative Examples 1-5 were reacted with cracked soft wax (>580°C fraction) in a fixed bed reactor for hydroisomerization reaction, and after the hydroisomerization reaction was completed, a supplementary refining reaction was performed to prepare lubricating oil base oil. The properties and distillation range distribution of the cracked soft wax are shown in Table 1.
[0176] The reaction conditions of hydroisomerization are: reaction temperature 330℃, volume space velocity 1h -1, hydrogen partial pressure 3 MPa, hydrogen to oil volume ratio 600: 1. The hydroisomerization catalyst is the hydroisomerization catalyst prepared in the above examples and comparative examples.
[0177] The reaction conditions for supplementary refining are: reaction temperature 240°C, hydrogen partial pressure 3Mpa, volume space velocity 1.2h -1 The volume ratio of hydrogen to oil is 700: 1. The supplementary refined catalyst is Pt-Pd / Al2O3 (purchased from Fuyan Institute of Precious Metals FMTA-2 Catalyst), and the total loading of Pt and Pd is 0.3wt% based on the carrier mass as 100%.
[0178] The yield, pour point, cloud point, viscosity index, oxidation stability of the lubricating oil base oil and the kinematic viscosity of the lubricating oil base oil of the fraction >530°C at 100°C were tested. The results are shown in Table 2.
[0179] 1. The specific surface area, pore volume and average pore size of the composite molecular sieve were measured by physical adsorption method BET test instrument (the instrument was purchased from Micromeritics, USA, model ASAP).
[0180] 2. The molar ratio of SiO2 to Al2O3 (silicon to aluminum ratio) was determined by X-ray fluorescence spectrometry.
[0181] 3. Yield = (mass of fraction > 300°C in isomerized product / mass of isomerized product) × 100%.
[0182] 4. The cloud point is measured by HCP852 automatic pour point / cloud point analyzer (made in Germany) according to the method of GB / T 6986-2014.
[0183] 5. The pour point is determined according to the method of GB / T 3535-2006.
[0184] 6. The viscosity index is measured according to the method of GB / T 1995.
[0185] 7. Oxidation stability is determined according to the method of SH / T 0193.
[0186] 8. The kinematic viscosity of lubricating oil base oil with a fraction of >530℃ at 100℃ is measured in accordance with the method of GB / T 265.
[0187] Table 1
[0188]
[0189]
[0190] Table 2
[0191]
[0192] Test Example 2
[0193] The hydroisomerization catalysts prepared in Example 2, Example 4, Example 5 and Comparative Example 1 were subjected to hydroisomerization reaction with refined wax (>580°C fraction) in a fixed bed reactor, and supplementary refining reaction was performed after the hydroisomerization reaction was completed. The properties and distillation range distribution of the refined wax are shown in Table 3.
[0194] The reaction conditions of hydroisomerization are: reaction temperature 340℃, volume space velocity 1h -1 , hydrogen partial pressure 4 MPa, hydrogen-to-oil volume ratio 800:1, and the hydroisomerization catalyst is the hydroisomerization catalyst prepared in the above-mentioned Example 2, Example 4, Example 5, and Comparative Example 1.
[0195] The reaction conditions for supplementary refining are: reaction temperature 240°C, hydrogen partial pressure 4MPa, volume space velocity 1.2h -1 The volume ratio of hydrogen to oil is 800: 1. The supplementary refined catalyst is Pt-Pd / Al2O3 (purchased from Fuyan Institute of Precious Metals FMTA-2 Catalyst), and the total loading of Pt and Pd is 0.3wt% based on the carrier mass as 100%.
[0196] The yield, pour point, cloud point, viscosity index, oxidation stability of the lubricating base oil and the kinematic viscosity of the lubricating base oil of the fraction >530°C at 100°C were tested. The test method was the same as that of Test Example 1. The results are shown in Table 4.
[0197] Table 3
[0198] Mass content (%) Distillation range(℃) Normal alkanes (wt%) ≥90% IBP / 5% 502 / 562 Non-normal alkanes (wt%) ≤10% 10% / 30% 584 / 617 Sulfur component none 50% / 70% 639 / 662 Nitrogen component none 90% / 95% 696 / 706 FBP 724
[0199] Table 4
[0200]
[0201] It can be seen from the experimental data of Examples 1-5 and Comparative Examples 1-3 that when the carrier of the hydroisomerization catalyst includes a composite molecular sieve, and the composite molecular sieve includes a core and a shell, and the shell is coated on the outer surface of the core, the hydroisomerization reaction is carried out with cracked soft wax (>580°C fraction) as the raw material, and the mass yield of the fraction >300°C in the obtained isomerized product is high, and the obtained lubricating oil base oil has a low pour point, a high kinematic viscosity, a low turbidity point, a high viscosity index, and good oxidation stability. When the composite molecular sieve in the hydroisomerization catalyst does not have a core-shell structure, not only the mass yield of the fraction >300°C in the isomerized product is low, but also the performance of the lubricating oil base oil is significantly reduced, which is specifically manifested in that the lubricating oil base oil has a high pour point, a low kinematic viscosity, a high turbidity point, a low viscosity index, and poor oxidation stability. Similarly, when the hydroisomerization reaction is carried out with refined wax (>580°C fraction) as the raw material, the same results are shown.
[0202] It can be seen from the experimental data of Examples 6 and 7 and Comparative Examples 4 and 5 that when the mass ratio of the outer shell to the inner core in the composite molecular sieve is 1: (1 to 10), the performance of the hydroisomerization catalyst is excellent, the mass yield of the fraction >300°C in the obtained isomerized product is high, and the obtained lubricating oil base oil has a low pour point, a high kinematic viscosity, a low cloud point, a high viscosity index, and good oxidation stability. When the mass ratio of the outer shell to the inner core in the composite molecular sieve is changed, the mass yield of the fraction >300°C in the isomerized product is significantly reduced, and the performance of the lubricating oil base oil is reduced, which is specifically manifested in an increase in pour point, a decrease in kinematic viscosity, an increase in cloud point, a decrease in viscosity index, and a deterioration in oxidation stability.
[0203] It can be seen from the experimental data of Examples 8-11 that when the mass ratio of active metal to carrier is 0.3-0.5:100, the performance of the hydroisomerization catalyst is excellent, the mass yield of the fraction >300°C in the obtained isomerized product is high, and the obtained lubricating base oil has a low pour point, a high kinematic viscosity, a low cloud point, a high viscosity index, and good oxidation stability. When the mass ratio of active metal to carrier is changed, the mass yield of the fraction >300°C in the isomerized product is significantly reduced, and the performance of the lubricating base oil is reduced, which is specifically manifested in an increase in pour point, a decrease in kinematic viscosity, an increase in cloud point, a decrease in viscosity index, and a deterioration in oxidation stability.
[0204] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0205] The hydroisomerization catalyst provided in the present application includes a carrier and an active metal. The hydroisomerization catalyst is a bifunctional catalyst. The active metal can provide metal sites for hydrogenation and dehydrogenation. The carrier is a composite molecular sieve with a core-shell structure. The composite molecular sieve formed by the synergistic interaction of an outer shell and an inner core in a specific mass ratio can promote the isomerization reaction, so that Fischer-Tropsch heavy wax (>580°C) shows a higher yield during hydroisomerization, and the prepared lubricating oil base oil has a lower pour point, a higher viscosity index, and excellent oxidation stability.
[0206] Therefore, the present application adopts a composite molecular sieve with a core-shell structure as a carrier and loads active metals on its surface. The formed hydroisomerization catalyst improves the selectivity of the hydroisomerization product, thereby preparing a lubricating oil base oil with a lower pour point, higher viscosity and good oxidation stability in the process of catalyzing the hydroisomerization of Fischer-Tropsch heavy wax (>580°C).
Claims
1. A hydroisomerization catalyst, characterized in that: The hydroisomerization catalyst comprises a carrier and an active metal supported on the carrier, wherein the carrier comprises a composite molecular sieve; the composite molecular sieve comprises an inner core and an outer shell, and the outer shell is coated on the outer surface of the inner core; the mass ratio of the outer shell to the inner core is 1:(1-10); the inner core comprises a ZSM series molecular sieve and / or a SAPO series molecular sieve, and the outer shell comprises a ZSM series molecular sieve and / or a SAPO series molecular sieve.
2. The hydroisomerization catalyst according to claim 1, characterized in that The mass ratio of the active metal to the carrier is 0.3-0.5:
100.
3. The hydroisomerization catalyst according to claim 1, characterized in that The ZSM series molecular sieves include at least one of ZSM-22, ZSM-23 and ZSM-48. And / or, the SAPO series molecular sieves include at least one of SAPO-11 and SAPO-31; Preferably, the composite molecular sieve comprises at least one of ZSM-48 / ZSM-48, SAPO-11 / ZSM-48, ZSM-23 / ZSM-48, and ZSM-22 / ZSM-48.
4. The hydroisomerization catalyst according to any one of claims 1 to 3, characterized in that The specific surface area of the composite molecular sieve is 230 to 300 m 2 / g; And / or, the pore volume of the composite molecular sieve is 0.2 to 0.6 cm 3 / g; And / or, the average pore size of the composite molecular sieve is 3 to 10 nm; And / or, the weak acid content of the composite molecular sieve is 0.10-0.30 mmol / g, and the medium-strong acid content is 0.05-0.25 mmol / g.
5. The hydroisomerization catalyst according to any one of claims 1 to 3, characterized in that The carrier also includes a binder; Preferably, the binder is pseudo-boehmite; Preferably, in the carrier, the mass ratio of the composite molecular sieve to the binder is (50-70): (50-30).
6. A method for preparing a hydroisomerization catalyst, characterized in that: The following steps are involved: A carrier is provided, a precursor solution containing active metals is mixed with the carrier, the active metals are loaded on the carrier, and a hydroisomerization catalyst is obtained by calcining once; wherein the carrier comprises a composite molecular sieve.
7. The preparation method according to claim 6, characterized in that: The preparation method of the composite molecular sieve comprises the following steps: Step S1, mixing a first aluminum source, a first silicon source, a first alkali source, a first template, an optional first phosphorus source and water to form a gel A, and crystallizing the gel A once to obtain a crystallized product A; Step S2, mixing a second aluminum source, a second silicon source, a second alkali source, a second template, an optional second phosphorus source and water to form a gel B, and performing secondary crystallization on the gel B to obtain a crystallized product B; Step S3, mixing the crystallized product A and the crystallized product B, performing three crystallizations, and performing two calcinations to obtain a composite crystallized product; Step S4, sequentially subjecting the composite crystallization product to alkali treatment and / or acid treatment, ion exchange with an ammonium salt solution, and drying to obtain a composite molecular sieve.
8. The preparation method according to claim 7, characterized in that: In the step S1, the temperature of the primary crystallization is 100 to 180° C., and the time of the primary crystallization is 10 to 60 hours; And / or, in the step S2, the temperature of the secondary crystallization is 100-180° C., and the time of the secondary crystallization is 10-60 hours; And / or, in the step S3, the mass ratio of the crystallized product A to the crystallized product B is 1:(1-10); And / or, in step S3, the time of the three crystallizations is 100-180° C., and the time of the three crystallizations is 6-48 hours; And / or, in step S3, the temperature of the secondary calcination is 500-600° C., and the time of the secondary calcination is 6-10 hours; And / or, in step S4, the temperature of the alkali treatment is 50-80° C., and the time of the alkali treatment is 2-5 hours; And / or, in step S4, the temperature of the acid treatment is 50-80° C., and the time of the acid treatment is 2-5 hours; And / or, in step S4, the concentration of the ammonium salt solution is 1-2 mol / L; And / or, in the step S4, the mass ratio of the composite crystallization product to the ammonium salt solution is 1:15-20; And / or, in step S4, the ammonium salt solution includes at least one of an ammonium chloride solution and an ammonium nitrate solution; And / or, in step S4, the temperature of the ion exchange is 70-80° C., and the time of the ion exchange is 2-4 hours.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The carrier also includes a binder, and the preparation method of the carrier includes: mixing the composite molecular sieve and the binder and molding to obtain the carrier; wherein the binder is pseudo-boehmite; Preferably, the mass ratio of the composite molecular sieve to the binder is (50-70): (50-30); and / or, the mass ratio of the active metal to the carrier is 0.3 to 0.5:100; And / or, the precursor solution containing active metals includes at least one of chloroplatinic acid solution, tetraammineplatinum dichloride solution, tetraammineplatinum dinitrate solution, and palladium chloride solution; And / or, the temperature of the first calcination is 350-500° C., and the time of the first calcination is 4-6 hours.
10. Use of the hydroisomerization catalyst according to any one of claims 1 to 5 or the hydroisomerization catalyst obtained by the preparation method according to any one of claims 6 to 9 in hydroisomerization of Fischer-Tropsch heavy wax, characterized in that: The Fischer-Tropsch heavy wax includes refined wax and / or cracked soft wax; The reaction conditions of the hydroisomerization are as follows: reaction temperature is 280-360°C, hydrogen partial pressure is 2-10 MPa, volume space velocity is 0.1-2 h -1 , the volume ratio of hydrogen to oil is (200~1500):1.
Citation Information
Patent Citations
Method for preparing lubricating oil base oil from Fischer-Tropsch hydrocracking tail oil
CN112111300A
Method for preparing high-viscosity lubricant base oil
CN117625238A
Cited By
Preparation method and application of a core-shell structure platinum-based catalyst
CN122895037A